Affective responses mediate the body language of penalty taker - decision-making relationship from soccer goalkeepers - Laurin, R.; Pellet, J. (Research Quarterly for Exercise and Sport, 2024)
ABSTRACT Purpose: Previous studies have shown that penalty-takers` body language affects the impressions that goalkeepers form about them and their anticipation performance. This research aimed to replicate these results and test the mediating effect of threat/challenge responses on the relationship between impression formation and the quality of goalkeeper decision-making.